2016
DOI: 10.7863/ultra.15.09046
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Index Variability in Anterior Cerebral Artery Measurements During Daily Transcranial Duplex Sonography

Abstract: Resistive index variability of 10% or greater on any day had a statistically significant risk of cerebrovascular complication development. Extracorporeal membrane oxygenation cannulation at younger than 3 days conferred an increased risk of cerebrovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Right parietal cortex had greater disruptions in autoregulation than the left parietal cortex, which may be related to right-sided cannulation of the common carotid artery and internal jugular vein. 107 Obstructions in cephalic venous drainage may affect autoregulation by increasing the ICP. 49 Further studies are needed on the effects of carotid and jugular ECMO cannulae on cerebrovascular hemodynamics.…”
Section: Extracorporeal Membrane Oxygenation (Ecmo)mentioning
confidence: 99%
“…Right parietal cortex had greater disruptions in autoregulation than the left parietal cortex, which may be related to right-sided cannulation of the common carotid artery and internal jugular vein. 107 Obstructions in cephalic venous drainage may affect autoregulation by increasing the ICP. 49 Further studies are needed on the effects of carotid and jugular ECMO cannulae on cerebrovascular hemodynamics.…”
Section: Extracorporeal Membrane Oxygenation (Ecmo)mentioning
confidence: 99%
“…In this overall context, CA impairment in critically ill patients treated by ECMO may be a key factor in the genesis of neurological complications. Recent preliminary studies using different methods have suggested an association with CA disorders and neurological outcome among children supported by ECMO (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring technology has not been developed along with ECMO-related technologies, and monitoring of the central nervous system is particularly challenging. The head ultrasound was used in patients undergoing ECMO with several limitations ( 16 , 17 ), for example, this approach could not capture the neurologic imaging in pediatric patients with closed cranial fontanels and adult patients ( 8 ). Besides, it cannot be used for continuous monitoring.…”
Section: Discussionmentioning
confidence: 99%